Combined Glaucoma Tube Shunt (Ahmed) and Fluocinolone Acetonide (Retisert™) Implantation Compared to Ahmed Alone in Uveitic Glaucoma. Issue 2 (December 2016) - Zivney, Mark; Lin, Phoebe; Edmunds, Beth; Parikh, Mansi; Takusagawa, Hana; Tehrani, Shandiz
Abstract Introduction Glaucoma is a known complication of uveitis, and may require glaucoma tube shunt implantation for intraocular pressure (IOP) control. The success of glaucoma tube shunt implantation in the setting of a local ocular steroid depot in uveitic glaucoma remains unknown. The purpose of this study was to determine whether patients who underwent combined glaucoma tube shunt (Ahmed) and fluocinolone acetonide (Retisert™, Bausch + Lomb, Bridgewater, NJ, USA) implantation have superior outcomes compared to patients with Ahmed implants only in the setting of uveitic glaucoma. Methods All participants were studied retrospectively and underwent Ahmed implantation alone or with existing/concurrent Retisert implantation (combined group) at a single academic institution. The main outcome measures were IOP, visual acuity (VA), number of IOP-lowering medications, and adverse events at 6 months after Ahmed implantation. Secondary outcome measures included adverse events and surgical success at 6 months after Ahmed implantation. Results Mean IOP at 6 months after Ahmed implantation was 15.3 ± 4.8 and 15.1 ± 4.9 mm Hg in the Ahmed only group (n = 17) and the combined group (n = 17), respectively (p = 0.89). The mean number of IOP-lowering medications at 6 months after Ahmed implantation was 1.7 ± 1.0 and 1.8 ± 1.0 in the Ahmed only group and the combined group, respectively (p = 0.86). Mean VA at 6 months after Ahmed implantation was 0.35 ± 0.29 and 0.42 ± 0.33 log mean angle of resolution in the Ahmed only group and the combined group, respectively (p = 0.50). No significant differences in surgical success or adverse events were noted between the two groups. Conclusion At 6 months, no significant differences in mean IOP, mean number of IOP-lowering medications, VA, surgical success, or adverse events were noted between Ahmed implantation alone or combined Ahmed and Retisert implantation in patients with uveitic glaucoma.